Desain Pesan Dalam Meningkatkan Keaktifan dan Hasil Belajar Peserta didik melalui model pembelajaran Discovery Learning: Desain Pesan Dalam Meningkatkan Keaktifan dan Hasil Belajar Peserta didik melalui model pembelajaran Discovery Learning - MERI, MERI; Evi Tri Prihatini; Trisya Sumiati; Warneri; Aunurrahman (Universitas Hamzanwadi, 2024)
The classroom action research was conducted due to the low level of activity and low learning outcomes, as teachers still applied conventional methods, namely lectures. The aim of this research is to increase student activity and learning outcomes. This research uses a discovery learning model with classroom action research methods carried out in 3 cycles. Stages of planning, implementation, observation and reflection. There were 38 people in Class XII MIPA SMA Negeri 4 Pontianak as research subjects. Data collection techniques using observation, testing, and documentation. The results of the first cycle showed activity in the low category, namely 43.60% with complete learning outcomes of only 47.36%. In the second cycle, 63.15% were in the medium category with 60.52% completeness and increased significantly in the third cycle, namely 80.07%, including the high category and learning outcomes with 81.57% completeness. It can be concluded that the discovery learning model was successful in increasing student activity and learning outcomes.